Emergency department utilisation by older people in metropolitan Melbourne, 2008?12: findings from the Reducing Older Patient. - Mazza, D.; Pearce, C.; Joe, A.; Turner, L.; Brijnath, Bianca; Browning, C.; Shearer, M.; Lowthian, J. (CSIRO Publishing, 2017)
Objective Older patients are over-represented in emergency departments (ED), with many presenting for conditions that could potentially be managed in general practice. The aims of the present study were to examine the characteristics of ED presentations by older patients and to identify patient factors contributing to potentially avoidable general practitioner (PAGP)-type presentations.Methods A retrospective analysis was performed of routinely collected data comprising ED presentations by patients aged =70 years at public hospitals across metropolitan Melbourne from January 2008 to December 2012. Presentations were classified according to the National Healthcare Agreement definition for PAGP-type presentations. Presentations were characterised according to patient demographic and clinical factors and were compared across PAGP-type and non-PAGP-type groups.Results There were 744519 presentations to the ED by older people, of which 103471 (13.9%) were classified as PAGP-type presentations. The volume of such presentations declined over the study period from 20893 (14.9%) in 2008 to 20346 (12.8%) in 2012. External injuries were the most common diagnoses (13761; 13.3%) associated with PAGP-type presentations. Sixty-one per cent of PAGP-type presentations did not involve either an investigation or a procedure. Patients were referred back to a medical officer (including a general practitioner (GP)) in 58.7% of cases.Conclusion Older people made a significant number of PAGP-type presentations to the ED during the period 2008-12. A low rate of referral back to the primary care setting implies a potential lost opportunity to redirect older patients from ED services back to their GPs for ongoing care.What is known about the topic? Older patients are increasingly attending EDs, with a proportion attending for problems that could potentially be managed in the general practice setting (termed PAGP-type presentations).What does this paper add? This study found that PAGP-type presentations, although declining, remain an important component of ED demand. Patients presented for a wide array of conditions and during periods that may indicate difficulty accessing a GP.What are the implications for practitioners? Strategies to redirect PAGP-type presentations to the GP setting are required at both the primary and acute care levels. These include increasing out-of-hours GP services, better triaging and appointment management in GP clinics and improved communication between ED clinicians and patients' GPs. Although some strategies have been implemented, further examination is required to assess their ongoing effectiveness.